The Moderating Role of Innovativeness on the Relationship between Entrepreneurship Educations And Student Entrepreneurial Intention - Najafi Auwal Ibrahim PhD & Muhammed Yazeed, Sani Aliyu Abubakar (Covenant Journal of Entrepreneurship, 2018)
This study examined the moderating role of innovativeness on the relationship between entrepreneurship education and students' entrepreneurial intention among FUD final year students as at 2017/2018 academic session. The study used a cross-sectional research design with a quantitative questionnaire approach to collect the data. To validate the model, data from 282 final year students were analyzed using the Partial Least Squares Structural Equation Modelling (PLS-SEM). Overall, the survey discovered that both entrepreneurship education and innovativeness are significantly and positively connected to entrepreneurial intention. This report also discovered that innovativeness play a part in moderating the entrepreneurship education and entrepreneurial intention relationship. The study used Human Capital Theory HCT as a theoretical basis of the subject. This survey served as one of the pioneering study with regard to HCT in a testing relationship of this nature. This study recommended that other researchers should employ this hypothesis with other antecedent of entrepreneurial intention for further proof. As a repercussion to policy, the government ought to guarantee not only inspiring students with entrepreneurship education, but also the robust spirit of innovativeness among students as it delivers a direct effect as well as strong interaction with entrepreneurship education in influencing students' entrepreneurial intention.